Comprehensive Ayurvedic Management of Diabetic Neuropathy: A Clinical Case Report - FARSEENA K,; SHAILESH DESHPANDE, (The Bioscan, 2025)
Diabetes mellitus is a chronic multisystem disease with diverse clinical presentations and complications. Among these, diabetic neuropathy is a significant complication that can profoundly affect a patient’s daily routine and mental well-being, thereby reducing their quality of life. Persistent hyperglycaemia is a major contributing factor to the development of diabetic neuropathy. Early detection and timely management are crucial to mitigate its progression and associated distress. This case report presents a 52-year-old male with type 2 diabetes mellitus who reported burning sensation in the soles as the only clinical manifestation of diabetic neuropathy. The patient underwent comprehensive Ayurvedic management, including internal medications and Panchakarma therapies, like Udwarthana, Dashamoolaksheera dhara, Abhyanga, Pizhichil and Ksheera vasthi. Significant improvement was observed in the patient’s symptoms and overall health, highlighting the potential of integrative Ayurvedic treatment approaches in addressing diabetic neuropathy. This case emphasizes the importance of early intervention and a holistic approach to improve patient outcomes and quality of life.